KEANEKARAGAMAN JENIS KELELAWAR (Chiroptera) DI HUTAN KOTA TELUK AKAR BERGANTUNG KABUPATEN KETAPANG - Trecyana, Lana; Dewantara, Iswan; Erianto, . (Universitas Tanjungpura, 2019)
Bats (Chiroptera) are the only mammals that can fly. Bat habitats are in caves, large trees in the forest, hollow trees, coconut trees, banana trees and roofs of buildings. Bats are nocturnal, they forage at night and sleep during the day by hanging upside down. Teluk Akar Bergantung has a generally flat and swampy topography, with a small portion submerged in water. Various types of trees have grown, one of them is Beringin/Kayu Are, which is where bats live. Bats play a role in the balance of ecosystems as seed dispersers, flower pollinators, insect controllers and guano producers. Based on the potential in this area, the research aims to collect data on various types of bats in Teluk Akar Bergantung, Ketapang regency, West Kalimantan. The method used is catch and release method using mist nest. Data analysis of the research used bats identification guide written by Suyanto (2001) entitled â€œKelelawar di Indonesiaâ€ and â€œPanduan Lapangan Mamalia di Kalimantan, Sabah, Sarawak dan Brunei Darussalamâ€ by Payne et. al (2000), diversity index (Hâ€™), equitability index (e), dominance index and species richness (d). The result of research obtained 14 individuals consist of 6 species (Vampir palsu (Megaderma spasma), Codot mini (Cynopterus minutus), Codot krawar (Cynopterus bracyothis), Codot horsfield (Cynopterus horsfieldii), Codot kecil kelabu (Pentethor lucasii) and Codot pisang-coklat (Macroglossus minimus), belonging to 2 families (Pteropodidae and Megadermatidae). Diversity index is in the medium category (1,47), the equitability index is in the high category (0,82), no type of bats that dominates (0,31) and the species richness is in medium category (2,79).Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: bats, diversity, Teluk Akar Bergantung, urban forest